1996
DOI: 10.1128/jb.178.24.7187-7196.1996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pelZ, a gene of the pelB-pelC cluster encoding a new pectate lyase of Erwinia chrysanthemi 3937

Abstract: The phytopathogenic enterobacterium Erwinia chrysanthemi 3937 produces five major and several secondary endo-pectate lyases encoded by the pel genes. Most of these genes are arranged in clusters on the bacterial chromosome. The genomic region surrounding the pelB-pelC cluster was supposed to be involved in the regulation of PelB and PelC synthesis. We demonstrated that the variation of pelB expression resulted from the titration of a regulatory protein by the gene adjacent to pelC. This gene was renamed pelZ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 47 publications
(54 reference statements)
1
53
0
Order By: Relevance
“…Several pectate lyases from mesophilic bacteria, above all from members of the genus Erwinia but also from the gram-positive genus Bacillus, have been cloned and characterized (Pissavin et al 1996;Tardy et al 1997;Shevchik et al 1997;Bauer and Collmer 1997;Soriano et al 2000). Recently, a thermostable pectate lyase from a newly isolated thermophilic bacterium, Thermoanaerobacter italicus, has been isolated and characterized (Kozianowski et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several pectate lyases from mesophilic bacteria, above all from members of the genus Erwinia but also from the gram-positive genus Bacillus, have been cloned and characterized (Pissavin et al 1996;Tardy et al 1997;Shevchik et al 1997;Bauer and Collmer 1997;Soriano et al 2000). Recently, a thermostable pectate lyase from a newly isolated thermophilic bacterium, Thermoanaerobacter italicus, has been isolated and characterized (Kozianowski et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The pelA-E-D cluster also includes the gene pemA, encoding the major pectin methylesterase. The transcription of pemA and of the five major pel genes is sensitive to several environmental conditions (Hugouvieux-CottePattat et al, 1996). The main factor affecting their expression is induction in the presence of pectin, resulting from the intracellular formation of catabolic products such as 2-keto-3-deoxygluconate (KDG).…”
Section: Introductionmentioning
confidence: 99%
“…They were detected only when bacteria were grown on plant material or in synthetic medium with macerated plant extracts (29,263,412). Three genes, pelL, pelZ; and pelI, encoding three of these secondary pectate lyases, were cloned and characterized from a derivative of E. chrysanthemi strain 3937 (301,387,449). Transcription of all three genes was inducible by plant extracts as well as by pectate catabolic products.…”
Section: Vol 69 2005mentioning
confidence: 99%
“…Different pel genes are also expressed at different levels during infection and appear to be differentially regulated depending on the host plant and even on the types of tissues (113,300,311). It is well established that each Pel enzyme has particular properties (301,387,449) and may play specialized roles during infection. It has been shown that the role of each pectate lyase depends on the host plant (29,41), suggesting that the variety of Pel isoenzymes may result from specific adaptations of the bacteria to macerate different plant tissues.…”
Section: Other Environmental Signals That Affect the Expression Of Pementioning
confidence: 99%
See 1 more Smart Citation